The barley chloroplast mutator (cpm) mutant: all roads lead to the Msh1 gene - Lencina, Franco Daniel (2022)
The barley chloroplast mutator (cpm) is a nuclear gene mutant that induces a wide spectrum of cytoplasmically inherited chlorophyll deficiencies. Plastome instability of cpm seedlings was determined by identification of a particular landscape of polymorphisms that suggests failures in a plastome mismatch repair (MMR) protein. In Arabidopsis, MSH genes encode proteins that are in charge of mismatch repair and have anti-recombination activity. In this work, barley homologs of these genes were identified, and their sequences were analyzed in control and cpm mutant seedlings. A substitution, leading to a premature stop codon and a truncated MSH1 protein, was identified in the Msh1 gene of cpm plants. The relationship between this mutation and the presence of chlorophyll deficiencies was established in progenies from crosses and backcrosses. These results strongly suggest that the mutation identified in the Msh1 gene of the cpm mutant is responsible for the observed plastome instabilities. Interestingly, comparison of mutant phenotypes and molecular changes induced by the barley cpm mutant with those of Arabidopsis MSH1 mutants revealed marked differences.